Pengembangan Instrumen Pengukur Keterampilan Guru dalam Mengajar Berbasis Media Pembelajaran (Loose Part) di Lembaga PAUD Jawa Tengah: Development of Teacher Skill Measurement Instruments in Teaching Based on Learning Media (Loose Part) in PAUD Institutions in Central Java - Dyah Kusbiantari; Sahrul; Sri Marfu’ah; Yeni Sundari; Salwa Asysyifaa Salsabila; Siti Sumarni; Yaniatu Hujjatunnafiah; Lukmarti Mujianah; Winanti Nike Apriliawan (Universitas Ngudi Waluyo, 2025)
Early childhood children are great imitators and active learners where children build knowledge by playing and always active in exploring new knowledge, and have a high curiosity. Game media loose parts is a game material that can be moved, combined, and redesigned in various ways. This research is research Research and development (R&D) by developing instruments to measure teacher skills in teaching based on learning media (loose parts)The aim is to find out valid and reliable instruments. The subjects in this research were 34 PAUD institution teachers located in Central Java. The statement instrument developed consisted of 10 items to be tested, the results of data analysis using the Jamovi application version 2.4.14 in items number 1 to number 10 it is more than (>) 0.3291, meaning that the instrument is said to be valid, based on the analysisdata Item Reliability Statistics from item 1 to item 10 it is more than(>) 0.6 then the instrument can be said to be reliable, seen from the tableScale Reliability Statistics Cronbach's α there is 0.761 with an Average (Mean) of 7.87%, then the instrumentmeasuring teacher skills in teaching using media (loose parts) good for use in the field and can be developed by students. ABSTRAK Anak usia dini sebagai peniru yang ulung dan pembelajar aktif dimana anak tersebut membangun pengetahuan melalui bermain dan selalu aktif menggali berbagai pengetahuan baru, serta memiliki rasa ingin tahu yang tinggi Media permainan loose parts merupakan suatu bahan permainan yang dapat dipindahkan, digabungan, dan dirancang ulang dengan berbagai cara. Penelitian ini merupakan penelitian Research and development (R&D) dengan mengembangkan instrumen pengukur keterampilan guru dalam mengajar berbasis media pembelajaran (loose parts),tujuannya untuk mengetahui instrumen yang valid dan reliabilitas. Subyek dalam penelitian ini guru lembaga PAUD berlokasi di jawa tengah dengan jumlah 34 orang. Instrumen pernyataan yang dikembangkan terdiri 10 item untuk diujikan, hasil analisis data menggunakan aplikasi Jamovi versi 2.4.14 pada item nomor 1 sampai dengan nomor 10 sudah lebih dari (>) 0,3291 artinya instrumen tersebut dikatakan valid, berdasarkan analisis data Item Reliability Statistics dari item 1 sampai dengan item 10 sudah lebih dari (>) 0,6 maka instrumen dapat dikatakan reliabilitas, dilihat dari tabel Scale Reliability Statistics Cronbach's α terdapat 0,761 dengan Rata-rata (Mean) 7,87%, maka instrumen pengukur keterampilan guru dalam mengajar menggunakan media (loose parts) baik digunakan di lapangan dan dapat dikembangkan pada siswa.